The long-term development of temperate woodland creation sites: from tree saplings to mature woodlands. (3rd June 2021) - Fuentes-Montemayor, Elisa; Park, Kirsty J; Cordts, Kypfer; Watts, Kevin
Abstract: Tree planting is at the forefront of the current environmental agenda to mitigate climate change and tackle the biodiversity crisis. In the United Kingdom (UK), tree planting has been a priority for more than a century and has helped increase woodland cover from a historic low of 5 per cent at the beginning of the 20th century to a current figure of 13 per cent. However, we still know relatively little about the long-term development of woodland creation sites (particularly of native woodlands) over ecologically realistic timescales. We surveyed a chronosequence of 133 temperate woodland patches encompassing 106 woodland creation sites (10–160 years old) and 27 mature 'ancient' woodlands (>250 years old), using a combination of field surveys and remote sensing techniques to quantify vegetation structural changes associated with woodland development. Woodland creation sites displayed similar vegetation development patterns to those described for other woodland systems, i.e. a gradual transition as woodlands undergo 'stand initiation', 'stem exclusion' and 'understorey re-initiation' stages, and became more similar to 'ancient' woodlands over time. Structural heterogeneity, average tree size and tree density were the attributes that varied the most among woodland developmental stages. In general, structural heterogeneity and average tree size increased with woodland age, whilst tree density decreased as would be expected. Younger sites in stand initiation were strongly dominated by short vegetation, stem exclusion sites by taller trees and older sites had a more even vegetation height distribution. There was a large degree of overlap between the vegetation characteristics of woodlands in understorey re-initiation stages and older ancient woodlands (partly driven by a lack of regeneration in the understorey); these results suggest that it takes between 80 and 160 years for woodland creation sites to develop certain vegetation attributes similar to those of mature ancient woodlands included in this study. Woodland management practices to create canopy gaps and reducing grazing/browsing pressure to promote natural regeneration are likely to accelerate this transition, increase the structural heterogeneity and biodiversity value of woodland creation sites and enable adaptation and resilience to climate change.